Cell Types, Network Homeostasis, and Pathological Compensation from a Biologically Plausible Ion Channel Expression Model - O'Leary, Timothy; Williams, Alex H; Franci, Alessio; Marder, Eve (Cell Press (Elsevier), 2019)
A fundamental question in neuroscience is how neurons develop, control, and maintain their electrical signaling properties in spite of ongoing protein turnover and activity perturbations. We address this question using theory and computational modeling. From generic assumptions about the molecular biology underlying channel expression we derive a simple model and show how it encodes an 'activity set-point'. The model can generate diverse self-regulating cell types and relates correlations in conductance expression observed in vivo to underlying channel expression rates. Both synaptic as well as intrinsic conductances can be regulated to make a self-assembling central pattern generator network; thus network-level homeostasis can emerge from cell-autonomous regulation rules. Finally, we demonstrate that homeostatic regulation depends on the complement of ion channels expressed in cells: in some cases loss of specific ion channels can be completely compensated, in others the homeostatic mechanisms itself causes pathological loss of function.